Religious Identity Politics: A Necessity or a Need to Avoid - Andi Sitti Emeralda Ria; Hamzah Harun al-Rasyid; Andi Aderus (Golden Ratio of Social Science and Education, 2026)
The phenomenon of religious identity politics often arises in the context of multicultural societies, such as in Indonesia, where religion is used as a tool to achieve political goals. The formulation of this research problem is the extent to which religious identity politics affects social stability and harmony in a plural society. The aim is to analyze the role of religious identity politics in socio-political dynamics, both as a catalyst for social justice and as a trigger for polarization. This research uses a literature study method with a descriptive-analytical approach to review relevant academic literature. The theory of pluralism and majority domination is used as an analytical framework to understand religious identity politics' potential benefits and risks. The results show that religious identity politics can be an effective tool to fight for the rights of marginalized groups. However, its excessive use can exacerbate inter-group polarization and conflict. In conclusion, religious identity politics should be managed with the principles of inclusivity and policies oriented toward the common good to prevent social fragmentation.